2020
DOI: 10.1002/jbmr.4046
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass, Bone Microstructure and Biomechanics in Patients with Hand Osteoarthritis

Abstract: The impact of primary hand osteoarthritis (HOA) on bone mass, microstructure, and biomechanics in the affected skeletal regions is largely unknown. HOA patients and healthy controls (HCs) underwent high‐resolution peripheral quantitative computed tomography (HR‐pQCT). We measured total, trabecular, and cortical volumetric bone mineral densities (vBMDs), microstructural attributes, and performed micro–finite element analysis for bone strength. Failure load and scaled multivariate outcome matrices from distal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
15
2
1
Order By: Relevance
“…AnhanddesHR-pQCTisteineDarstellungderKnochenmikro struktur und Knochengeometrie sowie eine volumetrische Kno chenmineraldichtemessung am distalen Radius sowie im Bereich derMetakarpophalangealgelenkeII-IVdurchführbar [16].Diege wonnenenvolumetrischenKnochenmineraldichtemessdatenkönn ten hier in Bezug auf die Gesamtknochenmineraldichte, trabeku läre Knochenmineraldichte und kortikale Knochenmineraldich tedifferenziertwerden [17].DasVerfahrenzeigteinesehrgute Reproduzierbarkeit(Knochengeometrie-Variationskoeffizient: 0,2 % -2,5 %; Mikrostruktur des trabekulären Knochens -Variati onskoeffizient:0,7%-2,4%;Knochenmineraldichte-Variations koeffizient:0,6%-1,7%undkortikaleDicke-Variationskoeffizient: 1,1%-1,3%) [18].…”
Section: Hochauflösende Periphere Quantitative Computertomografieunclassified
“…AnhanddesHR-pQCTisteineDarstellungderKnochenmikro struktur und Knochengeometrie sowie eine volumetrische Kno chenmineraldichtemessung am distalen Radius sowie im Bereich derMetakarpophalangealgelenkeII-IVdurchführbar [16].Diege wonnenenvolumetrischenKnochenmineraldichtemessdatenkönn ten hier in Bezug auf die Gesamtknochenmineraldichte, trabeku läre Knochenmineraldichte und kortikale Knochenmineraldich tedifferenziertwerden [17].DasVerfahrenzeigteinesehrgute Reproduzierbarkeit(Knochengeometrie-Variationskoeffizient: 0,2 % -2,5 %; Mikrostruktur des trabekulären Knochens -Variati onskoeffizient:0,7%-2,4%;Knochenmineraldichte-Variations koeffizient:0,6%-1,7%undkortikaleDicke-Variationskoeffizient: 1,1%-1,3%) [18].…”
Section: Hochauflösende Periphere Quantitative Computertomografieunclassified
“…Advanced technology such as high-resolution peripheral quantitative computed tomography (HRpQCT) provides new insight into the impact that HOA has on bone microarchitecture and to date there have been limited in vivo studies in this area. A recent study reported on the HRpQCT changes at the second metacarpal head (MCP2) and radius between healthy individuals and HOA patients [ 7 ]. While the study was relatively small, it suggested that clinical HOA was associated with reduced trabecular and increased cortical bone mass in the MCP2 head [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported on the HRpQCT changes at the second metacarpal head (MCP2) and radius between healthy individuals and HOA patients [ 7 ]. While the study was relatively small, it suggested that clinical HOA was associated with reduced trabecular and increased cortical bone mass in the MCP2 head [ 7 ]. Our study aims to extend these findings by describing the relationship between radiographic HOA and HRpQCT measures of the hand, wrist, and radius in a population-based study of older adults.…”
Section: Introductionmentioning
confidence: 99%
“… 9 - 18 Subchondral sclerosis is common in late-stage OA; however, some studies have observed thinning of the subchondral plate with increased porosity and deteriorated subchondral trabeculae with decreased bone density in early-stage OA. 15 , 19 - 22 Therefore, the role of subchondral bone in OA remains unclear.…”
Section: Introductionmentioning
confidence: 99%